Hidden by the name: A new fluorescent pumpkin toadlet from the Brachycephalus ephippium group (Anura: Brachycephalidae) - Nunes, Ivan; Guimarães, Carla S.; Moura, Pedro Henrique A G; Pedrozo, Mariana; Moroti, Matheus de Toledo; Castro, Leandro M.; Stuginski, Daniel R.; Muscat, Edelcio (Public Library of Science (PLoS), 2021)
Species of Brachycephalus has been having taxonomical issues due its morphological similarity and genetic conservatism. Herein, we describe a new species of Brachycephalus from the south Mantiqueira mountain range and semidecidual forests in the municipalities of Mogi das Cruzes, Campinas and Jundiaí, state of São Paulo, Brazil, based on an integrative approach. It can be distinguished from all species of the B. ephippium species group based on morphological characters (especially osteology and head shape), advertisement call and divergence in partial mitochondrial DNA gene sequences (16S). The new species is genetically similar to B. margaritatus and morphologically similar to B. ephippium. It can be differentiated from B. ephippium by the presence of dark faded spots on skull and post-cranial plates, presence of black connective tissue connective tissue scattered over dorsal musculature, parotic plate morphology, smaller snout-vent length (adult SVL: males 13.46-15.92 mm; females 16.04-17.69 mm) and 3% genetic distance. We also present natural history data and discuss the robustness of the integrative approach, geographic distribution, genetic data, behaviour, fluorescence in ontogeny, and conservation status.